Phosphorylation of eukaryotic initiation factor-2α promotes the extracellular survival of obligate intracellular parasite Toxoplasma gondii - Joyce, Bradley R. (National Academy of Sciences, 2010)
While seeking a new host cell, obligate intracellular parasites, such as the protozoan Toxoplasma gondii, must be able to endure the stress of an extracellular environment. The mechanisms Toxoplasma use to remain viable while deprived of a host cell are not understood. We have previously shown that phosphorylation of Toxoplasma eukaryotic initiation factor-2α (TgIF2α) is a conserved response to stress. Here we report the characterization of Toxoplasma harboring a point mutation (S71A) in TgIF2α that prevents phosphorylation. Results show that TgIF2α phosphorylation is critical for parasite viability because the TgIF2α-S71A mutants are ill-equipped to cope with life outside the host cell. The TgIF2α-S71A mutants also showed a significant delay in producing acute toxoplasmosis in vivo. We conclude that the phosphorylation of TgIF2α plays a crucial role during the lytic cycle by ameliorating the stress of the extracellular environment while the parasite searches for a new host cell.